DEVELOPMENT OF STUDENTS' SPATIAL IMAGINATION IN GEOMETRY LESSONS - Gulnora Goyibnazarova (Modern American Journals, 2026)
This article is devoted to the application of the idea of fusionism in teaching geometry. A fusionist approach to the presentation of a school geometry course. Stages of primary school students mastering geometric material. The idea of fusionism is the formation of ideas about the shape and relative position of figures, familiarization with regular polyhedra and regular polygons in a school geometry course.
Keywords: Fusionism, teaching geometry, stages of development, geometric figures, images of figures, planimetry, stereometry.